2009
DOI: 10.1007/s00464-009-0641-x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping as a side-effect of colonoscopic tattooing

Abstract: Our findings support the thesis that colonoscopic tattooing holds the potential for SLN mapping. Therefore, a prospective study with an appropriate case number should follow this pilot study to clarify the clinical value of this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
9
2
Order By: Relevance
“…It is questionable if tattooing has additional detection power as a sentinel LN mapping tool in T1 colorectal cancer. However, it should be mentioned that the median number of carbon-containing LNs per each person in our study (median 13, range 2-27) was higher than that in previous reports (median [5][6] [7,18]. Further large-scale studies are warranted to reveal the true impact of tattooing as a sentinel lymph node mapping tool.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It is questionable if tattooing has additional detection power as a sentinel LN mapping tool in T1 colorectal cancer. However, it should be mentioned that the median number of carbon-containing LNs per each person in our study (median 13, range 2-27) was higher than that in previous reports (median [5][6] [7,18]. Further large-scale studies are warranted to reveal the true impact of tattooing as a sentinel lymph node mapping tool.…”
Section: Discussioncontrasting
confidence: 72%
“…Several authors reported the possibility of tattooing as a useful tool for sentinel lymph node mapping [7,18]. Recently, Yan et al reported the endoscopic submucosal injection of 1 mL carbon nanoparticles suspension at the tumor site is feasible to detect sentinel lymph nodes in clinically T1-2 colorectal cancers [19].…”
Section: Discussionmentioning
confidence: 99%
“…We applaud Dr. Spatz and colleagues' appreciation of the clinical phenomenon that mesocolonic nodes often become carbon stained after endoscopic inking of the primary colonic lesion and their subsequent endeavour to progress the empiric toward evidence [1]. We also have noticed many patients who have undergone similar lesional tattooing who then have blackened nodes clearly evident in their mesentery at the time of definitive laparoscopic resection (Fig.…”
Section: Dear Sirmentioning
confidence: 99%
“…9 Colonoscopic tattooing also could serve as a method for sentinel LN mapping, although it might not discriminate between first and second echelon nodes. 10 The aim of sentinel LN mapping in CRC is not to reduce the extent of the resection, as is common practice in breast cancer surgery, but it refines staging by marking the LNs most likely to contain metastases. These specific nodes can then be subjected to more labor-intensive staging methods by the pathologist, such as multiple sectioning and immunohistochemical analysis, thereby increasing the percentage of patients staged at N1 8 by detecting occult tumor cells.…”
mentioning
confidence: 99%